Glaze composition and preparation method thereof
By using a combination of Li2O, ZnO, SrO and B2O3 to replace zinc oxide in the glaze, the glaze layer defects caused by excessive zinc oxide are solved, and better glaze performance and cost reduction are achieved.
Patent Information
- Application Number
- CN202411331479.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
AI Technical Summary
Excessive amount of zinc oxide in glaze will affect the moltenness and form glaze layer defects. Poor quality zinc oxide will lead to glaze defects, increase production costs, and affect product competitiveness.
The combination of Li2O, ZnO, SrO and B2O3 is used to replace zinc oxide. By controlling the proportion of these raw materials, the melting state of the glaze is improved, the glaze surface defects are reduced, and the cost is reduced.
The basic elimination of glaze defects is achieved, the gloss is improved, the coefficient of thermal expansion is reduced, the adhesion and acid resistance is enhanced, and the cost is reduced by more than 30%.
Smart Images

Figure BDA0005057069780000081 
Figure BDA0005057069780000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field and relates to a glaze composition and a preparation method thereof. Background Art
[0002] Zinc oxide is an important component in glazes, and is generally used in an amount of 5-10wt%. It plays a role in fluxing, reducing the thermal expansion coefficient, and giving the glaze layer a higher gloss. However, excessive zinc oxide (more than 10wt%) will affect the meltability and will also form willemite crystals or zinc spinel, making the glaze layer appear opaque.
[0003] Zinc oxide has different purity due to different production methods. There are two main production methods: (1) Indirect method, zinc oxide is obtained by oxidizing the vapour emitted by zinc ingots. Different particle sizes can be obtained during the manufacturing process and it is of high quality. (2) Direct method, zinc oxide is obtained from ore. It contains impurities such as iron oxide, cadmium oxide and lead oxide and is of poor quality. Poor quality zinc oxide also contains zinc sulfate, which will cause defects in the glaze.
[0004] Although zinc oxide can play a big role in glaze, poor quality zinc oxide will have a bad effect on the glaze surface. Therefore, high-end daily-use porcelain and sanitary ceramics have high requirements for zinc oxide quality to ensure product quality and safety. However, this also increases production costs and affects product competitiveness.
[0005] Therefore, the high cost of zinc oxide has always been a challenge facing the industry. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a glaze composition and a preparation method thereof.
[0007] The technical solution of the present invention is as follows:
[0008] A glaze composition, based on 100% by weight, the raw material components are a combination of 58.0%-68.0% SiO2, 2.0%-12.0% Al2O3, 0.1%-5.0% CaO, 0.1%-5.0% MgO, 1.0%-6.0% K2O, 0.5%-10.0% Na2O, 1.0%-10.0% La2O3, 1.0%-10.0% CeO2, and the remainder Li2O, ZnO, SrO and B2O3.
[0009] Preferably, the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 3.0% and not more than 25.0%.
[0010] More preferably, the weight percentage of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 5.0% and not more than 22.0%.
[0011] Preferably, the weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%.
[0012] More preferably, the weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not higher than 25.0%.
[0013] Preferably, the weight proportion of Li2O in the combination of Li2O, ZnO, SrO and B2O3 is not less than 3.0% and not more than 10.0%.
[0014] Preferably, the weight proportion of SrO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%.
[0015] Preferably, the weight percentage of Li2O in the glaze composition is 0.5%-2.0%.
[0016] Preferably, the weight percentage of ZnO in the glaze composition is 1.0%-6.0%.
[0017] The method for preparing the glaze composition described in any of the above embodiments comprises selecting quartz powder, potassium feldspar powder, kaolin, borax, zinc oxide, calcium carbonate, magnesium carbonate, strontium carbonate, lithium carbonate, cerium oxide and lanthanum oxide according to the raw material components, mixing them evenly, crushing and sieving them, melting them at high temperature, quenching and crushing them into a frit, and then grinding and crushing the frit to prepare the glaze composition;
[0018] Alternatively, according to the raw material components, strontium carbonate, zinc oxide, lithium carbonate and borax are mixed evenly, crushed and sieved, melted at high temperature, and quenched into a premix; quartz powder, potassium feldspar powder, kaolin, calcium carbonate, magnesium carbonate, cerium oxide, lanthanum oxide and the premix are selected, mixed evenly, crushed and sieved, melted at high temperature, and quenched into a frit, and then the frit is ground and crushed to make the glaze composition.
[0019] The beneficial effects of the present invention are:
[0020] (1) The glaze composition of the present invention combines the characteristics of four raw material components, namely, Li2O, ZnO, SrO and B2O3, and the four raw material components work synergistically to improve the melting state of the glaze composition under sintering, make the fluxing effect more obvious, basically eliminate the defects of the glaze surface, make the raw material components more evenly distributed, and make the glaze surface have higher gloss but do not cause light pollution. It has a lower thermal expansion coefficient, better adhesion, and stronger acid resistance. In addition, compared with pure zinc oxide, the cost can be reduced by more than 30%.
[0021] (2) Since the combination of Li2O, ZnO, SrO and B2O3 has a good fluxing effect, the glaze composition can be sintered at a lower temperature and a glaze layer with good performance can be obtained.
[0022] (3) By controlling the amount of Li2O and ZnO with higher costs in a lower range, the combination of Li2O, ZnO, SrO and B2O3 can replace zinc oxide with better efficacy and lower cost. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0024] In order to find a substitute for zinc oxide in a glaze composition to reduce the cost and further improve the performance of the glaze, on the one hand, the present invention provides a glaze composition, wherein the raw material components are 58.0%-68.0% SiO2, 2.0%-12.0% Al2O3, 0.1%-5.0% CaO, 0.1%-5.0% MgO, 1.0%-6.0% K2O, 0.5%-10.0% Na2O, 1.0%-10.0% La2O3, 1.0%-10.0% CeO2, and the remainder are Li2O, ZnO, SrO and B2O3, based on 100% by weight.
[0025] In the glaze composition of the present invention, a combination of Li2O, ZnO, SrO and B2O3 is used to replace ZnO. B2O3 has a strong fluxing effect, which can reduce the viscosity and surface tension of the glaze under sintering, and is helpful to reduce glaze defects. A small amount of Li2O can significantly reduce the amount of Na2O and K2O, and improve the durability and acid resistance of the glaze, reduce the thermal expansion coefficient, improve fluidity and glossiness, etc. A small amount of SrO can improve the fluidity of the glaze composition in the sintered state, has a significant fluxing effect, and reduces glaze defects and improves the adhesion of the glaze. In addition, the inventors have also found that although the four raw material components of Li2O, ZnO, SrO and B2O3 have some repetitive effects, such as fluxing, the combination of these four raw material components has a better effect, such as a more significant fluxing effect, and can also avoid the shortcomings of a single raw material component or the problems of excessive dosage. Therefore, using a combination of Li2O, ZnO, SrO and B2O3 to replace ZnO can not only reduce costs by more than 30%, but also after the glaze composition is glazed and sintered, the glaze surface is basically defect-free, the gloss is high but does not cause light pollution, and it has a lower thermal expansion coefficient, higher adhesion, and stronger acid resistance.
[0026] In a preferred embodiment of the present invention, the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 3.0% and not more than 25.0%. If the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is too low, the effect is not obvious, and if the weight proportion is too high, it will affect other properties. For example, the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition can be 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 23.0%, 24.0%, 25.0%, etc., without any particular limitation. In a more preferred embodiment, the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 5.0% and not more than 22.0%. Further preferably, the weight proportion of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 8.0% and not more than 20.0%.
[0027] In a preferred embodiment of the present invention, the weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%. In addition to the fluxing effect, zinc oxide can also improve the glaze strength and reduce the thermal expansion coefficient in the glaze composition. Controlling the weight proportion of zinc oxide can control the cost of the glaze composition, but the weight proportion of zinc oxide cannot be too low, otherwise it will affect the performance of the glaze. For example, the weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 can be any value of 10.0%, 12.0%, 15.0%, 18.0%, 20.0%, 22.0%, 25.0%, 27.0%, 30.0%, etc., without special restrictions. In a more preferred embodiment, the weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not higher than 25.0%.
[0028] In a preferred embodiment of the present invention, the weight proportion of Li2O in the combination of Li2O, ZnO, SrO and B2O3 is not less than 3.0% and not more than 10.0%. Although the price of lithium raw materials in glaze raw materials is relatively expensive, it has special advantages. The atomic weight of lithium is small, and a small amount of lithium can replace a large amount of potassium and sodium atoms. In theory, 1g of lithium can replace 3-5g of potassium or sodium, which can reduce the amount of alkali, improve the fluidity of glaze, reduce the firing melting time, enhance the durability of glaze, reduce its thermal expansion rate, increase acid resistance, etc. For example, the weight proportion of Li2O in the combination of Li2O, ZnO, SrO and B2O3 can be any value of 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc., without special restrictions.
[0029] In a preferred embodiment of the present invention, the weight proportion of SrO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%. Adding a small amount of strontium compound to the glaze raw materials can improve the melting state and play a fluxing role. It can also improve the glossiness of the glaze surface and increase the acid resistance, crack resistance, scratch resistance and water solubility. For example, the weight proportion of SrO in the combination of Li2O, ZnO, SrO and B2O3 can be any value of 10.0%, 12.0%, 15.0%, 18.0%, 20.0%, 22.0%, 25.0%, 27.0%, 30.0%, etc., without special restrictions.
[0030] In a preferred embodiment of the present invention, the weight proportion of Li2O in the glaze composition is 0.5%-2.0%. For example, the weight proportion can be any value of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc., without any particular limitation.
[0031] In a preferred embodiment of the present invention, the weight proportion of ZnO in the glaze composition is 1.0%-6.0%. For example, the weight proportion can be any value of 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, etc., without special limitation. Or further, the weight proportion of ZnO in the glaze composition is 2.0%-5.0%.
[0032] On the other hand, the present invention also provides a method for preparing the glaze composition described in any of the above embodiments, wherein quartz powder, potassium feldspar powder, kaolin, borax, zinc oxide, calcium carbonate, magnesium carbonate, strontium carbonate, lithium carbonate, cerium oxide and lanthanum oxide are selected according to the raw material components, mixed evenly, crushed and sieved, melted at high temperature, quenched into a frit, and then the frit is ground and crushed to make a glaze composition;
[0033] Alternatively, according to the raw material components, strontium carbonate, zinc oxide, lithium carbonate and borax are mixed evenly, crushed and sieved, melted at high temperature, and quenched into a premix; quartz powder, potassium feldspar powder, kaolin, calcium carbonate, magnesium carbonate, cerium oxide, lanthanum oxide and premix are selected, mixed evenly, crushed and sieved, melted at high temperature, and quenched into a molten block, and then the molten block is ground and crushed to make a glaze composition.
[0034] By pre-melting the raw materials of Li2O, ZnO, SrO and B2O3, lithium carbonate, zinc oxide, strontium carbonate and borax, into a premix, the combined efficacy of Li2O, ZnO, SrO and B2O3 can be further exerted, resulting in better performance.
[0035] The glaze composition of the present invention can be mixed with water and ground before use to form a glaze slurry, which is then applied to the surface of a ceramic body and sintered at a high temperature to form a glaze layer.
[0036] The technical solution of the present invention is further described and illustrated according to various embodiments below.
[0037] Example 1
[0038] The glaze composition, by weight, comprises 61.2% SiO2, 7.2% Al2O3, 2.3% CaO, 3.1% MgO, 2.7% K2O, 3.2% Na2O, 2.6% La2O3, 2.7% CeO2, and 15.0% Li2O+ZnO+SrO+B2O3. In the combination of Li2O+ZnO+SrO+B2O3, based on the weight of the combination of Li2O+ZnO+SrO+B2O3, the weight of Li2O accounts for 6.0%, the weight of ZnO accounts for 20.0%, and the weight of SrO accounts for 20.0%.
[0039] According to the above raw material components and the weight of each raw material component, quartz powder, potassium feldspar powder, kaolin, borax, zinc oxide, calcium carbonate, magnesium carbonate, strontium carbonate, lithium carbonate, cerium oxide and lanthanum oxide are mixed evenly, crushed and passed through a 60-mesh sieve, melted at a high temperature of 1250-1300°C, put into water and quenched into a frit, and then the frit is ground and crushed to make a glaze composition.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that in embodiment 1, the raw material components of the combination of Li2O+ZnO+SrO+B2O3 are pre-mixed uniformly and passed through a 60-mesh sieve, melted at a high temperature of 1150-1200°C, quenched and crushed into a premix, and the premix is then mixed with the remaining raw material components. The remaining steps remain unchanged.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that the weight proportion of ZnO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 10.0%, and the weight proportion of B2O3 is increased accordingly. The other steps remain unchanged.
[0044] Example 4
[0045] The difference between this embodiment and embodiment 1 is that the weight proportion of ZnO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 10.0%, and the weight proportion of SrO is increased accordingly. The other steps remain unchanged.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is that the weight proportion of ZnO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 25.0%, and the weight proportion of B2O3 is reduced accordingly. The other steps remain unchanged.
[0048] Example 6
[0049] The difference between this embodiment and embodiment 1 is that the weight proportion of ZnO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 25.0%, and the weight proportion of SrO is reduced accordingly. The remaining steps remain unchanged.
[0050] Example 7
[0051] The difference between this embodiment and embodiment 1 is that the weight proportion of SrO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 10.0%, and the weight proportion of B2O3 is increased accordingly. The other steps remain unchanged.
[0052] Example 8
[0053] The difference between this embodiment and embodiment 1 is that the weight proportion of SrO in the combination of Li2O+ZnO+SrO+B2O3 is adjusted from 20.0% to 30.0%, and the weight proportion of B2O3 is reduced accordingly. The remaining steps remain unchanged.
[0054] Example 9
[0055] The difference between this embodiment and embodiment 1 is that the weight percentage of the combination of Li2O+ZnO+SrO+B2O3 in the glaze composition is adjusted from 15.0% to 10.0%, and the weight percentage of B2O3 is increased accordingly. The other steps remain unchanged.
[0056] Example 10
[0057] The difference between this embodiment and embodiment 1 is that the weight proportion of the combination of Li2O+ZnO+SrO+B2O3 in the glaze composition is adjusted from 15.0% to 20.0%, and the weight proportions of the other raw material components are reduced accordingly. The other steps remain unchanged.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that the weight proportion of the combination of Li2O+ZnO+SrO+B2O3 in the glaze composition is adjusted from 15.0% to 28.0%, and the weight proportions of the other raw material components are reduced accordingly. The other steps remain unchanged.
[0060] Comparative Example 2
[0061] The difference between this comparative example and Example 1 is that in the combination of Li2O+ZnO+SrO+B2O3, the weight percentage of SrO is adjusted from 20.0% to 0, and the weight percentage of B2O3 is increased accordingly. The other steps remain unchanged.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 1 is that in the combination of Li2O+ZnO+SrO+B2O3, the weight percentage of SrO is adjusted from 20.0% to 40.0%, and the weight percentage of B2O3 is reduced accordingly. The other steps remain unchanged.
[0064] Comparative Example 4
[0065] The difference between this comparative example and Example 1 is that the weight percentage of the combination of Li2O+ZnO+SrO+B2O3 in the glaze composition is adjusted from 15.0% to 0, and the weight percentages of the other raw material components are increased accordingly. The other steps remain unchanged.
[0066] Comparative Example 5
[0067] The difference between this comparative example and comparative example 1 is that the combination of ZnO+SrO+B2O3 is pre-mixed uniformly and passed through a 60-mesh screen, melted at a high temperature of 1150-1200°C, quenched and crushed into a premix, and the premix is then mixed with the remaining raw material components. The remaining steps remain unchanged.
[0068] Performance Testing
[0069] The glaze composition to be tested is added to water and ground to obtain a glaze slurry. The glaze slurry has a specific gravity of 1.85-1.90 g / mL, a solid particle fineness of 0.04% of the residue on a 10,000-hole sieve, a glaze amount of 320±10 g / ㎡ on the ceramic body, and is sintered at 1100-1150°C and 1250-1300°C for 2 hours.
[0070] Glaze prickly heat defects: Count the number and size of prickly heat within 1 square meter and observe the smoothness of the glaze layer. The fewer prickly heat defects on the glaze, the higher the smoothness and the better the glaze quality.
[0071] Acid resistance: Soak in 4 vol% acetic acid at 60°C for 10 and 15 days, and test the solid dissolution. The lower the solid dissolution, the better the acid resistance.
[0072] The results are shown in Table 1 below.
[0073] Table 1
[0074]
[0075]
[0076] Therefore, the data in Table 1 above reflect that the glaze composition of the present invention can have a good sintering effect when sintered at a lower temperature and a higher temperature, and the glaze surface has no prickly heat defects, is smooth and delicate, and has good acid resistance. From the comparison of the results of the above embodiments and comparative examples, it can be seen that the combination of Li2O+ZnO+SrO+B2O3 in the glaze composition of the present invention can achieve a good sintering effect in a suitable ratio and range, and the glaze layer has a high quality.
[0077] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A glaze composition, characterized in that: Based on 100% by weight, the raw material components are a combination of 58.0%-68.0% SiO2, 2.0%-12.0% Al2O3, 0.1%-5.0% CaO, 0.1%-5.0% MgO, 1.0%-6.0% K2O, 0.5%-10.0% Na2O, 1.0%-10.0% La2O3, 1.0%-10.0% CeO2, and the remainder Li2O, ZnO, SrO and B2O3.
2. The glaze composition according to claim 1, characterized in that The weight percentage of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 3.0% and not more than 25.0%.
3. The glaze composition according to claim 2, characterized in that: The weight percentage of the combination of Li2O, ZnO, SrO and B2O3 in the glaze composition is not less than 5.0% and not more than 22.0%.
4. The glaze composition according to claim 1, characterized in that The weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%.
5. The glaze composition according to claim 4, characterized in that The weight proportion of ZnO in the combination of Li2O, ZnO, SrO and B2O3 is not higher than 25.0%.
6. The glaze composition according to claim 1, characterized in that: The weight proportion of Li2O in the combination of Li2O, ZnO, SrO and B2O3 is not less than 3.0% and not more than 10.0%.
7. The glaze composition according to claim 1, characterized in that: The weight proportion of SrO in the combination of Li2O, ZnO, SrO and B2O3 is not less than 10.0% and not more than 30.0%.
8. The glaze composition according to claim 1, characterized in that: The weight percentage of Li2O in the glaze composition is 0.5%-2.0%.
9. The glaze composition according to claim 1, characterized in that: The weight percentage of ZnO in the glaze composition is 1.0%-6.0%.
10. The method for preparing the glaze composition according to any one of claims 1 to 9, characterized in that: According to the raw material components, quartz powder, potassium feldspar powder, kaolin, borax, zinc oxide, calcium carbonate, magnesium carbonate, strontium carbonate, lithium carbonate, cerium oxide and lanthanum oxide are selected, mixed evenly, crushed and sieved, melted at high temperature, quenched into a frit, and then the frit is ground and crushed to make the glaze composition; Alternatively, according to the raw material components, strontium carbonate, zinc oxide, lithium carbonate and borax are mixed evenly, crushed and sieved, melted at high temperature, and quenched into a premix; quartz powder, potassium feldspar powder, kaolin, Calcium carbonate, magnesium carbonate, cerium oxide, lanthanum oxide and the premix are mixed evenly, crushed and sieved, The molten material is melted at high temperature, quenched and crushed into a frit, and then the frit is ground and pulverized to form the glaze composition.
Citation Information
Patent Citations
Lead-free ceramic glaze and preparation process thereof
CN101759440A
Enamel color ceramic glaze and production process and application thereof
CN101768016A
Lead-free and cadmium-free bone china glaze and preparation process thereof
CN101891501A
Leadless ceramic glaze and its preparation method
CN102515857A
Daily ceramic glaze and preparation method thereof
CN102515867A